Marine Sediments Processes, Transport and Environmental Aspects - Risio, Marcello Di; Hayes, Donald F.; Pasquali, Davide (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In recent years, increasing attention has been paid to water quality and environmental aspects related to sediment transport, driven by both ambient forcing and human activities. Estuarine, coastal, and harbor areas often undergo operations to nourish beaches, to maintain navigation channels, and to remove contaminated sediment. Hence, much research is needed related to the sediment processes, transport, and related environmental aspects of marine sediments. The aim of this Special Issue is to exhibit novel research results in this field. Particular attention is paid to water quality and environmental aspects relating to sediment transport driven by anthropogenic activities and natural phenomena: spillover due to tidal processes, metals mobility, coastal modifications driven by extreme events and mean wave climate, sediments re-suspension and dispersion related to marine sediment handling.